The significance of shape and orientation in single-particle weak-scatterer models. - Coussios, C (2002)
Particles that have a density and compressibility comparable to those of the surrounding medium (weak scatterers) are often modeled as spherical scatterers of equivalent volume. The simplicity and symmetry of the spherical model does not however account for the effect of the angle of incidence of the incident field onto the particle. By performing a comparative study of scattering models for the case of a fluid sphere, it is shown that models derived using the Born approximation closely match the exact solution for weak scatterers. This approximation is therefore applied to produce a model for the fluid disk, which is used to investigate the significance of particle shape and orientation. Scattering by a red blood cell of given volume modeled as a sphere is compared to the result obtained by approximating its shape as a disk of varying aspect ratio and orientation. The spherical model is shown to provide a good description for frequencies up to 20 MHz, beyond which particle shape becomes significant. This effect could go undetected if the scattered field is only observed at 90 degrees relative to the direction of the incident field. Nevertheless, the significance of particle shape and orientation might form the basis of a novel detection technique.